Platelets at the Vessel Wall in Non-Thrombotic Disease. Issue 6 (17th March 2023) - Aggarwal, Anu; Jennings, Courtney L.; Manning, Emily; Cameron, Scott J.
Abstract : Platelets are small, anucleate entities that bud from megakaryocytes in the bone marrow. Among circulating cells, platelets are the most abundant cell, traditionally involved in regulating the balance between thrombosis (the terminal event of platelet activation) and hemostasis (a protective response to tissue injury). Although platelets lack the precise cellular control offered by nucleate cells, they are in fact very dynamic cells, enriched in preformed RNA that allows them the capability of de novo protein synthesis which alters the platelet phenotype and responses in physiological and pathological events. Antiplatelet medications have significantly reduced the morbidity and mortality for patients afflicted with thrombotic diseases, including stroke and myocardial infarction. However, it has become apparent in the last few years that platelets play a critical role beyond thrombosis and hemostasis. For example, platelet-derived proteins by constitutive and regulated exocytosis can be found in the plasma and may educate distant tissue including blood vessels. First, platelets are enriched in inflammatory and anti-inflammatory molecules that may regulate vascular remodeling. Second, platelet-derived microparticles released into the circulation can be acquired by vascular endothelial cells through the process of endocytosis. Third, platelets are highly enriched in mitochondria that may contribute to the local reactive oxygen species pool and remodel phospholipids in the plasma membrane of blood vessels. Lastly, platelets are enriched in proteins and phosphoproteins which can be secreted independent of stimulation by surface receptor agonists in conditions of disturbed blood flow. This so-called biomechanical platelet activation occurs in regions of pathologically narrowed (atherosclerotic) or dilated (aneurysmal) vessels. Emerging evidence suggests platelets may regulate the process of angiogenesis and blood flow to tumors as well as education of distant organs for the purposes of allograft health following transplantation. This review will illustrate the potential of platelets to remodel blood vessels in various diseases with a focus on the aforementioned mechanisms.